ANALISIS KESIAPAN SISWA KELAS VI MENGGUNAKAN ALAT EVALUASI BERBASIS DIGITAL (KAHOOT) DI SDN 2 SIANGAN - A.A Istri Mahayoni Citrayanti; Putu Beny Pradnyana (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2025)
This study aims to explore the extent of physical and mental readiness of sixth-grade students at SD Negeri 2 Siangan in participating in digital learning evaluations using Kahoot. The method employed is a descriptive qualitative approach, with data collected through questionnaires distributed to 31 students. The data analysis results indicate that most students demonstrate good readiness, both physically and mentally. The majority of students possess good concentration skills, a high motivation to learn, and the ability to manage stress effectively. Although many students are already accustomed to using smartphones for learning, some are still unfamiliar with digital evaluation methods. Some students also face physical challenges, such as fatigue, despite having healthy sleep and eating patterns. These findings emphasize the importance of physical and mental readiness, as well as environmental support, in ensuring the success of digital learning evaluations. Further research is expected to explore in greater depth the impact of digital evaluations on students' academic performance.